Influence of Green Human Resource Management Practices on Employee Retention in the Hotel Industry - Adedayo Emmanuel Adeyefa; Abioye Adedipe; Ibidapo Natheniel Adebayo; Ayokanmi Jacob Adesuyan (African Journal of Hospitality, Tourism and Leisure, 2023)
This paper aimed to investigate employee retention rates in the hotel sector by evaluating the impact of green human resource practices (GHRM). This study utilised a combined method of Structural Equation Modelling (SEM) and Relative Importance Index (RII) to measure the efficiency of GHRM practices. A structured questionnaire involving 460 questions was shared to participants. The data was collected from low-level hotel employees with at least a year of working experience in a green practising hotel in Nigeria. The RII was calculated using the SPSS version 25, and the results revealed that GRS provides a higher RII to retaining employees than other practices. This research proposed GRS as the most effective GHRM policy to improve employee retention rates in the hotel sector. Also, SEM results reveal a significant positive influence of all independent variables on employee retention except GPR which is statistically positive but not significant. Also, SEM-RII method was combined to develop a more novel and robust analytical framework in the field of GHRM practices. GRS was found to be more effective for retention through the use of RII––an effort that has not been reported by any scholar which contribute to the current knowledge base for HRM and practice.